EFFECT OF REMIFENTANIL BOLUS VS FENTANYL IN ATTENUATING HEMODYNAMIC RESPONSE IN VIDEOLARYNGOSCOPIC ENDOTRACHEAL INTUBATION - Jalal, Shakho Jamal; Khudadad, Amir Murad (Journal of Sulaimani Medical College, 2025)
Background Elevation of blood pressure and pulse rate are hemodynamic changes that occur during general anesthesia as a consequence of laryngoscopy and endotracheal intubation ETI, different laryngoscopies and many drugs have been tried to reduce these changes. Objectives To evaluate and compare the efficacy of minimum dose of fentanyl and comparable remifentanil bolus dose during videolaryngoscopic ETI. Patients and Methods A triple blind randomized clinical trial implemented on 224 patients of age group between 16-65 years of either sex (ASA I and ASA II) scheduled for elective operation under general anesthesia with endotracheal intubation, they are randomly assigned into two groups, group A and group B representing both fentanyl and remifentanil as the drug preparation was unknown neither by the patient nor by the researcher and nor by the data analyser, in addition propofol two mg/kg and rocuronium 0.8 mg/kg were given then systolic blood pressure SBP, diastolic blood pressure DBP, mean arterial blood pressure MAP and heart rate HR were recorded in five different occasions as (T0) for baseline preinduction, (T1) one minute before ETI, (T2) one minute after ETI, (T3) three minutes after ETI and (T4) five minutes after ETI. Results There was a significant difference in the mean value of HR, SBP, DBP, MAP in both groups before, one, three and five minutes after endotracheal intubation with King vision videolaryngoscope KVVL and one μg/ kg remifentanil bolus administration (group B) effectively showed substantial reduction in all hemodynamic parameters with significant statistical result (P < 0.05) when compared to intravenous IV fentanyl one μg/kg (group A). Conclusion Remifentanil bolus of one μg/kg is better than intravenous fentanyl one μg/kg in attenuating hemodynamic response to ETI when KVVL used.
Keywords: Remifentanil; fentanyl; hemodynamic change; videolaryngoscope; tracheal intubation